Aktivitas Fisik dan Tingkat Stress dengan Siklus Menstruasi pada Mahasiswa FIKES UHAMKA - Hilda Nurfadilah; Izna Nurdianty Muhdar; Devieka Rhama Dhanny (Sarana Ilmu Indonesia (salnesia), 2022)
The menstrual cycle is the distance between the start date of the previous menstruation and the start of the next menstruation. Long-term menstrual cycle disorders can cause infertility, endometrial hyperplasia, long-term anovulation, anemia, and decreased quality of life. The menstrual cycle research was conducted on students of the Faculty of Health Sciences, University of Muhammadiyah Prof. Dr. Hamka(FIKES UHAMKA) because it was found that 46,9% of female students experienced menstrual cycle irregularities. The purpose of this study was to determine the relationship between physical activity and stress level with the menstrual cycle in student Faculty of Health sciences University of Muhammadiyah Prof. Dr. Hamka. This study used a cross-sectional design. The sample of this research was 146 samples taken by the technique of purposive sampling. Data analysis was performed using the statistical test Chi- Square. The result showed that most of the respondents had regular menstrual cycles 67,8%, moderate physical activity 67,8%, and moderate stress 82,9%. There was no relationship between physical activity (p=0,347) and stress level (p=0,821) with the menstrual cycle. Thus, physical activity or stress levels do not correlate to the menstrual cycle.